A Case Report: Fourth branchial cleft fistula successfully treated with microlaryngoscopic cauterization - Hunchaisri, Niran (Journal of Medicine and Health Sciences, 2009)
A 23-year-old man was presented with recurrent left-sided neck abscess which is characteristic clinical features of fourth branchial cleft fistula. The abscess burst spontaneously, forming a fistula. Diagnosis of fourth branchial fistula in this patient was verified by barium radiograph and injection of methylene blue into the external opening. An internal opening was found at the apex of the left piriform fossa. The current treatment of choice involves complete excision of the sinus tract. Endoscopic cauterization of the internal fistulous tract was developed by some authors. It offers several advantages over open excision such as less injuries to important structures. The cost and duration of treatment are also reduced. Microlaryngoscopic electric cauterization of the internal opening was used to close the fistula. There has been no recurrence of the cervical abscess during 10 months of follow-up. Therefore, microlaryngoscopic electric cauterization seems to be a safe treatment for patients with fourth branchial cleft fistulas.